Analisis Model Fusi Informasi Intelijen: Studi Kasus Informasi PPATK Tentang Pendanaan Terorisme di Indonesia - Fuad, Muhamad; Purwanto , Hari (Jurnal Keamanan Nasional, 2025)
The global security paradigm shifted after the Cold War from state security to human security, positioning terrorism as a primary non-traditional threat, particularly regarding its financing. Indonesia responded by establishing a legal framework and facilitating information exchange through PPATK to prevent terrorism financing. This study aims to analyze the model for fusing intelligence information using a PPATK case study to enhance the effectiveness of terrorism financing prevention through a fusion center approach. Theories applied include threat, intelligence, terrorism, terrorism financing, and information fusion. The research method is descriptive qualitative, utilizing interviews and literature studies. The analysis reveals the need for prioritization based on institutional urgency, fulfillment of 24-hour information delivery, and early prevention. The implementation of the Suspected Terrorism Financing Information System has proven effective in detection, prevention, and enforcement, enabling comprehensive tracking of terrorist networks. However, the development of a joint watchlist database remains necessary so that analytical results can support strategic decision-making in addressing the threat of terrorism financing in Indonesia